International Capital Transactions : Should They Be Restricted? - Fieleke, Norman (Washington, D.C. : International Monetary Fund, 1993)
Some prominent economists and officials contend that government restrictions should be used to limit international capital movements that are considered destabilizing. This paper briefly summarizes the recent usage of such restrictions, discusses their international acceptance and their theoretical justification, reviews recent empirical studies of their efficacy, and examines their efficacy in Ireland, Spain, and Portugal during the latter part of 1992. The conclusion is that such restrictions typically have no more than fleeting and minor success in attaining their objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet